1999
DOI: 10.1111/j.1365-2621.1999.tb12280.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional, Sensory, and Microbiological Properties of Restructured Beef and Emu Steaks

Abstract: Beef and emu steaks were restructured with 5% fibrinogen/0.25% thrombin (F), 0.5% algin/0.5% calcium lactate (A), or 0.5% phosphate/1.5% salt (P). P and A treatments had higher cooked binding strengths and cook yields than the F treatments (P < 0.05). The pH and cook yields of restructured emu were higher than beef (P < 0.05). Binding strength of emu was lower than beef in all binding systems (P < 0.05). F solution had an aerobic plate count (APC) of 39,000/g and increased the microbial count in restructured e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 11 publications
4
16
0
1
Order By: Relevance
“…Fibrimex TM treatments were also described as rubbery or chewy. Consumer studies comparing Fibrimex TM to alginate restructured beef steaks found that use of these binders resulted in similar texture ratings (Boles & Shand, 1999;Shao, et al, 1999).…”
Section: Consumer Evaluationmentioning
confidence: 95%
See 2 more Smart Citations
“…Fibrimex TM treatments were also described as rubbery or chewy. Consumer studies comparing Fibrimex TM to alginate restructured beef steaks found that use of these binders resulted in similar texture ratings (Boles & Shand, 1999;Shao, et al, 1999).…”
Section: Consumer Evaluationmentioning
confidence: 95%
“…TG was rated highest for overall liking (Pp0:05) while there was no difference between Fibrimex TM treatments. Shao, et al (1999) reported that a trained sensory panel rated Fibrimex TM beef and emu steaks lower for bind Table 4 Bind strength of cooked pork restructured with or Fibrimex TM (g/100 g) with sodium tripolyphosphate (g/100 g) or Activa TM TG-RM (g/100 g). 1: N is Newtons, J is Joules.2: Treatments were Control-10 ¼ 10 g/100 g Fibrimex TM ; STP ¼ pork restructured with 5 g/100 g Fibrimex TM and 3g/100 g sodium tripolyphosphate; TG ¼ pork restructured with Activa TM TG-RM transglutaminase.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that restructured beef steaks formulated with Fibrimex® produced a weaker bind compared with alginate. However, once cooked, Fibrimex® steaks were found to have a binding strength equal or stronger than that of steaks restructured with alginate [33,34]. Interestingly, other researchers have reported the binding strength of both raw and cooked steaks formulated with Fibrimex® to be stronger than those reformulated with alginate [35].…”
Section: Bindermentioning
confidence: 90%
“…The common method is to solubilise myofibrillar proteins with salt and the aid of tumbling process, and heat set them to form a stable protein gel matrix which binds the pieces together. Investigations relating to the process of restructuring beef (Ensor et al, 1990;Tsai et al, 1998;Shao et al, 1999;Tsao et al, 2002), pig (Motzer et al, 1998), poultry (Hongsprabhas and Barbut, 1999;Shao et al, 1999) and seafood products (Yetim and Ockerman, 1995a;Yetim and Ockerman, 1995b;Meinert et al, 1999;Ramírez et al, 2002;Tėllez-Luis et al, 2004) have been reported. Unlike meat-based restructured products sold frozen or cooked, most seafood products are sold raw and a market for cold-set binders has emerged.…”
mentioning
confidence: 99%